2013
DOI: 10.1093/gji/ggt074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of average stress drop measures for ruptures with heterogeneous stress change and implications for earthquake physics

Abstract: Stress drop, a measure of static stress change in earthquakes, is the subject of numerous investigations. Stress drop in an earthquake is likely to be spatially varying over the fault, creating a stress drop distribution. Representing this spatial distribution by a single number, as commonly done, implies averaging in space. In this study, we investigate similarities and differences between three different averages of the stress drop distribution used in earthquake studies. The first one, σ M , is the commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(198 citation statements)
references
References 42 publications
6
192
0
Order By: Relevance
“…Classical slip inversions are performed on large fault planes, often rectangular and planar, to allow the slip to be contained within the parameter space, such that the area of nonzero slip is smaller than the area of the fault chosen for the inversion. To better estimate the area where slip occurred, a threshold of slip is defined to constrain the minimum of slip required to count each pixel in the area [Noda et al, 2013], which can yield trimming factors between the area of most slip and the total fault surface [Somerville et al, 1999;Noda et al, 2013;Ye et al, 2016aYe et al, , 2016b.…”
Section: Static Stress Dropmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical slip inversions are performed on large fault planes, often rectangular and planar, to allow the slip to be contained within the parameter space, such that the area of nonzero slip is smaller than the area of the fault chosen for the inversion. To better estimate the area where slip occurred, a threshold of slip is defined to constrain the minimum of slip required to count each pixel in the area [Noda et al, 2013], which can yield trimming factors between the area of most slip and the total fault surface [Somerville et al, 1999;Noda et al, 2013;Ye et al, 2016aYe et al, , 2016b.…”
Section: Static Stress Dropmentioning
confidence: 99%
“…Noda et al [2013] differentiates three types of averaging, moment-based, area-based, and energy-based averaging, which agree if the stress drop is uniform on the fault. Note that the Noda et al [2013] study finds that moment-based stress drops likely underestimate the estimate of the average stress drop if the stress change is heterogeneous by up to a factor of 8. Brown et al [2015] confirms that stress drop varies strongly locally, and the choice of the threshold (trimming factor) especially affects total measures of stress drop.…”
Section: Static Stress Dropmentioning
confidence: 99%
“…S8) and integrating it weighted by the slip distribution using the slipweighted stress method (Noda et al, 2013). σ is estimated as 38 MPa.…”
Section: Radiated Energy Stress Drop and Radiation Efficiencymentioning
confidence: 99%
“…Unfortunately, it is difficult in practice to determine the slip distribution in sufficient detail to estimate its spatial distribution. Numerical models 18 have shown that Δ . We use 0.15 as the trimming parameter for all of our finite-fault models for the mainshock and aftershock.…”
Section: Finite-fault Model Inversionsmentioning
confidence: 99%